Foraging speed and precision of arbuscular mycorrhizal fungi under field conditions: An experimental approach - Šmilauer, Petr; Šmilauerová, Marie; Kotilínek, Milan; Košnar, Jiří (Molecular ecology, 2020)
To better understand the ecology of arbuscular mycorrhizal (AM) symbiosis, we need to measure functional traits of individual fungal virtual taxa under field conditions. The efficiency of AM fungi in locating nutrient-rich patches in soil space is one of their central traits in this symbiotic relationship. We used plots of a long-term field experiment in grassland with manipulated functional group composition of host plant community to establish ingrowth patches with substrate free of roots and fungi and with varying nutrient availability. Comparison of the original AM fungal community before patch creation with that present 9 weeks after patch establishment enabled us to estimate relative hyphal foraging speed for 41 fungal taxa, and a comparison of the fungal community in neighbouring patches differing in nutrient availability provided estimates of hyphal foraging precision for 22 taxa. Members of two dominant fungal families, Glomeraceae and Claroideoglomeraceae, differed in their foraging speed and precision. Glomeraceae taxa responded more slowly, but with a higher focus on enriched patches. We further demonstrated the usefulness of the obtained fungal functional traits by testing the differences between grass and dicotyledonous plant hosts using a data set obtained in another experiment at the same plots. Grass species hosted AM fungal communities with higher foraging speed, but lower foraging precision than the dicotyledonous species. Our study results support the use of field experiments for measuring comparative characteristics of AM fungi, which are highly elusive (or misrepresented) under controlled conditions.
Keywords: Glomeromycota; kořeny rostlin; symbióza; foraging speed; Symbiosis; houby; foraging precision; functional traits; mykorhiza; Soil Microbiology; soil nutrients; Fungi; půdní mikrobiologie; Mycorrhizae; půda; Plant Roots; Soil; lidé; Humans; Claroideoglomeraceae; Glomeraceae